Separation and Preparation Purine Alkaloids from Green Tea Waste - Li, Huai-Ping; Tan, He-Ping; Yao, Shun; Song, Hang (Asian Journal of Chemistry, 2012)
A simple, clean and economical method to separate and prepare purine alkaloids from green tea waste in one-step by Sephadex LH-20 column chromatography was developed. From extraction to separation and preparation, distilled water was used. The qualitative analysis of purine alkaloids was performed by time of flight mass spectrometer and the content was quantitatively analyzed by high-performance liquid chromatography. The yield of purine alkaloids was 3.37 % of the dry weight of green tea waste, which contained caffeine (93.01 %) and theobromine (6.92 %) and the recovery of purine alkaloids by column chromatography was 96.84 % and the stability of preparative method is good. The study was considered to be a promising clean method for purine alkaloids preparation without using poisonous organic solvents.